2019
DOI: 10.1186/s13601-019-0269-4
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-year follow-up study after endoscopic sinus surgery in patients with chronic rhinosinusitis with nasal polyposis

Abstract: Background Chronic rhinosinusitis with nasal polyposis (CRSwNP) is a therapeutic challenge because of the high recurrence rate. Surgical intervention should be considered in patients who fail to improve after medical treatment. We monitored recurrence and revision surgery over 12 years after endoscopic sinus surgery in CRSwNP patients. Methods In this prospective cohort study, 47 patients with CRSwNP, who underwent primary or revision extended endoscopic sinus surgery, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
150
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 160 publications
(157 citation statements)
references
References 27 publications
3
150
2
2
Order By: Relevance
“…FESS is a treatment option for CRS patients with uncontrolled disease despite pharmaceutical treatment 19 . Managing nasal polyps in CRSwNP patients remains a therapeutic challenge with recurrence rates at 1 year after FESS of 38% and at 12 years after surgery in up to 78.9% of patients 20,21 . In the latter study, revision surgery took place in 36.8% of patients over the 12‐year period 20 .…”
Section: Discussionmentioning
confidence: 98%
“…FESS is a treatment option for CRS patients with uncontrolled disease despite pharmaceutical treatment 19 . Managing nasal polyps in CRSwNP patients remains a therapeutic challenge with recurrence rates at 1 year after FESS of 38% and at 12 years after surgery in up to 78.9% of patients 20,21 . In the latter study, revision surgery took place in 36.8% of patients over the 12‐year period 20 .…”
Section: Discussionmentioning
confidence: 98%
“…The prevalence of uncontrolled CRSwNP among the general CRSwNP population is not reported in the literature. Only two studies from Belgium have reported 41.8% and 40% uncontrolled CRSwNP among the CRSwNP population who previously had surgery for NP 22,23 .…”
Section: Languagementioning
confidence: 99%
“…In recent years, there has been a significant increase in the number of diseases of the nose and paranasal sinuses both in absolute numbers and as a percentage of the total number of ear, nose and throat (ENT) diseases - [1,5]. According to some authors, over the past decade, the number of cases of sinusitis per 1000 people has increased from 4.6 to 12.2.…”
Section: Resultsmentioning
confidence: 99%
“…Factors that violate the patency of the natural openings of the paranasal sinuses and the mechanisms of their aeration and cleansing include abnormalities of the development of the nasal concha, curvature of the nasal septum, and deformation of the nasal valve, whose functions have not yet been fully studied [2,3,9,12]. The rendered pathological action creates the conditions for blockade of the ostiomeatal complex, and subsequently the development of the inflammatory process in the paranasal sinuses [4,5,6,7,9,11]. In conditions of stagnation of the secret and a decrease in the partial pressure of oxygen in the PNS, favorable conditions are created for the development of a bacterial infection [12,13,14,15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation